MANAJEMEN PEMBIAYAAN PENDIDIKAN DI PESANTREN PERSIS 99 RANCABANGO - Naqiya Salsabila; Suryadi; Fitroh Hayati (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
Educational financing management is a crucial aspect for the sustainability and quality of the education system, including in Islamic boarding schools that often face financial management challenges due to dependence on community donations, student fees, and fluctuating social assistance. Persis 99 Rancabango Islamic Boarding School, as an Islamic educational institution, is committed to creating quality education despite facing income instability. This research aims to understand how Islamic boarding schools manage education financing efficiently and effectively, and how adaptation to income fluctuations can improve the quality of education even with limited resources. This study uses a qualitative approach with a phenomenological approach. The researcher acted as the main instrument for collecting data through observation techniques, interviews and documentation studies with selected informants, namely the Islamic boarding school treasurer who was directly involved in financial management. Management of education financing at Pesantren Persis 99 Ranbataso involves four main aspects: planning, implementation, supervision and evaluation. The success of this Islamic boarding school lies in careful planning, diversity of funding sources, and transparent supervision in achieving effective Islamic boarding school financial management.